Solve the quadratic equation by completing the square. What are the missing pieces to the steps?

–27 = 4x2 – 24x

–27 = 4(x2 – 6x)

–27 + = 4(x2 – 6x + 9)

9 = 4(x – 3)2

= (x – 3)2

± = x – 3

= x

Respuesta :

Answer:

x = 1.5, 4.5

Step-by-step explanation:

We have to solve the equation by completing the square

-27 = 4x² - 24x

-27 = 4(x² - 6x)

By adding 36 on both the sides of the equation,

-27 + 36 = 4(x² - 6x + 9)

9 = 4(x - 3)²

Divide by 9 on both the sides of the equation,

[tex]\frac{9}{4}[/tex] = (x - 3)²

Now we take the square root on both the side of the equation,

[tex]\pm \frac{3}{2}[/tex] = (x - 3)

x = 3 ± 1.5

x = 1.5, 4.5

Answer:

36

3/2

3/2 & 9/2

Ver imagen skkskstemp